Living Hadis dalam Praktik Donasi Digital di Indonesia: Transformasi Sedekah dan Resepsi Muslim di Era Fintech - Zulfikar Zulfikar; Muhammad Zaid Alfaizi; Muh. Hasbil Baharuddin; Muharik Faqih; Fatchurrohman Anggara Rofi Al Hafidz (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2026)
The development of financial technology (fintech) has transformed the pattern of philanthropy among Indonesian Muslim society, particularly in charitable giving practices that are increasingly integrated with digital donation platforms. This phenomenon reflects a new transformation in the reception of hadiths concerning almsgiving, which were previously practiced predominantly through direct social relations. This study aims to analyze the forms of living hadith in digital donation practices, the transformation of charitable values, and Muslim society’s reception of hadiths on almsgiving in digital spaces. The study employs a qualitative method using a living hadith approach and socio-religious analysis. Data were collected through digital observation, documentation of online donation platforms such as Kitabisa, e-wallet donation features, mosque QRIS systems, and literature studies on hadith and digital Islamic philanthropy. The findings reveal that digital donation practices represent a new form of living hadith through the reproduction of narratives on the virtues of charity, the visualization of religious symbols, and social media-based philanthropic campaigns. The study also finds a shift in charitable practices from personal relations toward technology-based systems, including the transformation of secret charity into publicly displayed charity within digital spaces. In addition to expanding social participation among Muslims, the culture of digital donation has also contributed to the commodification of religiosity and the reception of hadiths shaped by social media logic and internet visual culture.